A new record of Licea tuberculata from Mexico. - Lizarraga Escobar, Marcos (2020)
A new record of a rare species of Licea from Mexico is described and illustrated herein. It is compared with other morphologically similar species. We provide micrographs of the most important characters as observed under LM and SEM.